A New Crosslinking Assay to Study Guanine Nucleotide Binding in the Gtr Heterodimer of S. cerevisiae. (31st December 2022) - Doxsey, Dylan D.; Veinotte, Kristen; Shen, Kuang
ABSTRACT: The mechanistic target of rapamycin (mTOR) complex is responsible for coordinating nutrient availability with eukaryotic cell growth. Amino acid signals are transmitted towards mTOR via the Rag/Gtr heterodimers. Due to the obligatory heterodimeric architecture of the Rag/Gtr GTPases, investigating their biochemical properties has been challenging. Here, we describe an updated assay that allows us to probe the guanine nucleotide-binding affinity and kinetics to the Gtr heterodimers in Saccharomyces cerevisiae . We first identified the structural element that Gtr2p lacks to enable crosslinking. By using a sequence conservation-based mutation, we restored the crosslinking between Gtr2p and the bound nucleotides. Using this construct, we determined the nucleotide-binding affinities of the Gtr heterodimer, and found that it operates under a different form of intersubunit communication than human Rag GTPases. Our study defines the evolutionary divergence of the Gtr/Rag-mTOR axis of nutrient sensing.